Non-perturbative solution of the Ginzburg-Landau equation - İnç, Mustafa; Bildik, N. (Assoc Sci Res, 2000)
The decomposition method is an effective method for solving a wide class of problems. This method requires less work if compared with the traditional techniques and does not require unjustified assumptions, linearization or perturbation. To give a clear overview of the methodology, the Ginzburg-Landau equation is taken as a one-homogeneous example.
Keywords: Approximation theory; Boundary conditions; Convergence of numerical methods; Integration; Polynomials; Decomposition method; Ginzburg-Landau equation; Partial differential equations